Secondary embryonary root associated with seed germination in Garcinia intermedia (Clusiaceae) and its possible role in seedling survival - Di Stefano, Jose Fsco. (2006)
Germination tests on Garcinia intermedia (Clusiaceae) seeds showedthe growth of two types of roots: additionally to the primary root, a secondary root crosses the seedlengthwise. To determine its possible role on the survival andgrowth of this species, 90 seedlings at least six months old(collectedin Central Costa Rica) were plantedin plastic bags with organic soil, andplacedin a greenhouse. The seedlings were treatedas follows: treatments in which the primary or secondary root was cut off, anda control group with both roots intact (30 replicates each). After three months 10 seedlings/month/treatment were extractedto measure their height, basal diameter, root length (main andsecondary root), andbiomass of the stem, roots andseed(without its coat). Control seedlings hadthe highest growth, followedby those without secondary roots. Nonetheless, more than 90% of the seedlings whose primary roots were cut off, survivedafter five months of the excision treatment, in part due to the capacity of this species to regenerate its radical systemthrough the seedreserves, sproutingof a primary-like root, and/or the growth stimulus of the secondary root (60% of the total: 20% with sprouts fromthe primary root stump, 13.3% with a growth stimulus of the secondary root, and26.7% with both conditions). The length of the sproutedroots was significantly different only on those plants that were extractedduringthe first two monthly measurements, when comparedwith the control (F6= 18.6, F7=16.0, p<0.01).